Health information-seeking behaviour on high-risk behaviour among adolescents - Ab Hakimee, Nabila Iezzah (Penerbit Universiti Sains Malaysia, 2023)
Background: The unique nature of adolescence makes youths highly susceptible to high-risk behaviours. Thus, prevention and health promotion are imperative for this influential age. Despite various approaches towards health promotion, knowledge related to adolescent health is still low among Malaysian adolescents. This study aims to investigate adolescent health information-seeking behaviours related to high-risk behaviours. Methods: A cross-sectional study was conducted among 370 adolescents aged 10 years old–19 years old throughout Malaysia. The questionnaire used was adapted from a previous study and the pilot study resulted in Cronbach’s alpha of 0.85. IBM SPSS Statistics version 25.0 software was used for data analysis at two statistical levels: descriptive and inferential (Mann-Whitney U test). Result: The most important health information needs related to high-risk behaviour according to the adolescents were ‘violence’ (3.72 score out of 5), ‘sexual activity-related disease’ (3.64 score out of 5) and ‘physical activity and effect of lack in physical activity’ (3.61 score out of 5). ‘Physician’ (4.01 score out of 5) and ‘the internet’ (3.95 score out of 5) were the most important sources for obtaining health information related to high-risk behaviours. The main criterion for the quality of health information was the ‘validity and reliability of the information’ (4.55 score out of 5). The findings indicate that adolescents have a positive attitude towards health information-seeking behaviour, although slight differences between boys and girls are exhibited. The most common barrier to health information seeking experienced by adolescents is ‘difficulty in determining the quality of information found’. Conclusion: Adolescents tend to use professional and informal sources, have good criteria in the selection of information and have a considerably high interest in seeking health information related to high-risk behaviour.